A 23-Year-Old Man with Hyper-IgM Syndrome Presenting with Asymptomatic Violaceous Facial Plaques - Mirelys Barrios; Neera Nathan; Ryan Trowbridge; Molly Plovanich; Rosalynn M. Nazarian; Daniela Kroshinsky (MDPI AG, 2020)
Tumid lupus is a rare subtype of chronic cutaneous lupus that is characterized by urticaria-like photosensitive plaques. Unlike discoid lupus, it has minimal to no surface change and resolves without scarring. On pathological examination, it may be distinguished from other types of lupus by abundant interstitial mucin deposits. Herein, we describe a case of tumid lupus in a 23-year-old Kuwaiti male with hyper-IgM syndrome. To our best knowledge, this is the first report of tumid lupus in a patient with a primary immunodeficiency.